Implementasi Inquiry Based Learning (IBL) pada Topik Gerak Lurus Beraturan (GLB) untuk Meningkatkan Intelectual Skill dan Penguasaan Konsep Siswa - Hendra, Taufik; Hurriyah, Hurriyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
This study aims to determine how the influence of Inquiry Based Learning (IBL) on the topic of Regular Straight Motion (GLB) to Improve Intellectual Skills and Concept Mastery in Class VIII Students. The research method used in this research is experimental research. The study population was 256 people. The sample used was random sampling, in order to obtain a sample of class VIII F of 32 students. The data collection technique used in this study was a test. The data analysis technique is the prerequisite test data analysis. Based on the results of the research conducted, it was found that there was an effect of Inquiry Based Learning (IBL) on the topic of Regular Straight Motion to Improve Intellectual Skills and Concept Mastery in Class VIII Students.Â